Maximizing co-products net income at Western Sugar - Hofer, Michael (Kansas State University, 2008)
The Western Sugar Cooperative is a 135,000 acre sugar beet processing cooperative headquartered in Denver, Colorado with sugar beet processing factories located in Ft. Morgan CO, Torrington WY, Scottsbluff NE, Lovell WY, and Billings MT. The objective of the thesis is to analyze alternatives for maximizing the net revenue of co-products at Western Sugar. The ethanol policies of the U.S. government have had many unintended consequences including increasing the price of corn which is a key ingredient in animal feed production. Sugar beet co-products are produced in fixed proportions. That is, for every unit of sugar produced a corresponding unit of sugar beet pulp is created which is mostly water. Historically this has been dried into an animal feed pellets, however removing water from any high volume and high speed manufacturing process is energy intensive. Natural gas prices have increased dramatically and are projected to stay that way for a long time. As a result, the cost of manufacturing pellets is very high. The research shows that we are able to significantly increase our net income by increasing the percentage and price of pressed feed pulp rather than drying the pulp into pellets. This equals 20 million dollars of revenue in our pulp product line for the 2008-2009 sugar beet campaign. The thesis contains various analyses for changes in critical costs and prices. More importantly it details the subsequent management decisions implemented to maximize net income in the co-products business.
Keywords: Co products; Pressed pulp; Agriculture, General (0473)